Networks, labour and migration among Indian Muslim artisans - Chambers, Thomas (Economic exposures in Asia., 2020)
Networks, Labour and Migration Among Indian Muslim Artisans provides an ethnography of life, work and migration in a North Indian Muslim-dominated woodworking industry.